PM2.5 and Heavy Metal Concentrations in Ambient Air of a Steel Industrial Zone: Influence of Meteorological Factors in Cilegon, Indonesia - Prinajati, Purnomosutji Dyah; Handayani, Lidia; Astuti, Nila (Department of Environmental Engineering - Universitas Pasundan - Indonesia, 2025)
This study was to examine the concentrations of PM2.5 and associated heavy metals (Fe, Pb, Zn, and Cd) in the ambient air of a steel industrial zone in Cilegon, Indonesia. Cilegon is recognized as a major industrial hub; however, comprehensive assessments of PM2.5 pollution in such heavy industry contexts remain limited. Air samples were collected from four strategic locations surrounding PT Krakatau Steel using a Sequential PM Sampler, and meteorological data were simultaneously recorded. Gravimetric analysis was applied to determine PM2.5 mass, while heavy metals were quantified via Inductively Coupled Plasma–Atomic Emission Spectroscopy (ICP-AES). The results of the study indicate that the concentrations of PM2.5 and related heavy metals (Fe, Pb, Zn, and Cd) in the ambient air of steel industry areas often exceed the WHO guideline (25 µg/m³) and, in some instances, approached or surpassed the Indonesian national standard (65 µg/m³), with higher values typically observed during periods of active industrial operations. Among the metals analyzed, iron (Fe) was dominant, indicating a strong link to steel processing activities. Spearman's correlation revealed a statistically significant positive relationship between ambient temperature and PM2.5 concentrations, while no significant correlation was found for relative humidity. These findings highlight the health risks associated with prolonged exposure to fine particulate matter and toxic metals, underscoring the urgent need for targeted air quality management and worker protection strategies in industrial zones. The study contributes local-scale evidence for environmental governance and public health policy in rapidly industrializing regions.